Análisis de imágenes digitales - Roman Gonzalez, Avid (2019)
A specific field of image processing focuses on the evaluation of image quality and assessment of their authenticity. A loss of image quality may be due to the various processes by which it passes. In assessing the authenticity of the image we detect forgeries, detection of hidden messages, etc. In this work, we present an overview of these areas; these areas have in common the need to develop theories and techniques to detect changes in the image that it is not detectable of visual way. Most of these methods use mutual information as a basis for image analysis. The satellite images are affected by artifacts, the artifact has a very similar characteristics to those mentioned above, an artifact is a disorder that almost cannot visually observe.